Understanding the Transport of Atmospheric Gases in Liquid Electrolytes for Lithium–Air Batteries. Issue 7 (1st July 2021) - Haas, Ronja; Murat, Michael; Weiss, Manuel; Janek, Jürgen; Natan, Amir; Schröder, Daniel
Abstract : In metal–air batteries, carbon dioxide (CO2 ) and nitrogen (N2 ) are, apart from oxygen (O2 ), also present as dissolved species in the liquid electrolyte. These dissolved gases can strongly influence the battery performance, as they affect the discharge mechanism and the stability of the lithium metal anode. Therefore, their solubility and diffusivity are important parameters, that are rarely considered in the development of electrolytes for metal–air batteries. In this work, the diffusion coefficients ( D ) and Henry's law solubility constants ( H cp ) of O2, N2 and CO2 in common ether-based (diglyme (2G), triglyme (3G) and tetraglyme (4G)) and DMSO-based electrolytes are measured by means of gas uptake measurements. Additionally, the diffusion coefficients are calculated through molecular dynamics simulations. The results agree well with the experimental data. Furthermore, the influence of solvent parameters, such as surface tension and viscosity, on the solubility and the diffusivity as well as the impact of the addition of LiTFSI as conducting salt are investigated. The reported data will help to assess the impact of dissolved gases on the cell chemistry of nonaqueous lithium–air batteries, especially on the solid electrolyte interphase (SEI) at the lithium anode, and to predict diffusivity and gas solubility in other electrolytes.